Shattered Ethics: Abandoned Objects as Ethical Affordances - Lovasz, Adam (Pivot: A Journal of Interdisciplinary Studies and Thought, 2017)
Abstract In this essay, we explore various manifestations of shatteredness and fractalized Being. Through a dense reading of recent social theory pertaining to ruins and abandoned, abject objects, we hope to show that an appreciation of ruined, wasted materiality can contribute to generating an ethics of hospitality and corporeal generosity. To contemplate the Other, we must resist the temptation to appropriate their alterity. Rather, the irreducible alterity of shattered objects should be recognized. Objects are independent of our own intentionalities. Abandoned objects and sites constitute ethical affordances, opportunities for an ethical practice predicated upon abandoning ourselves to these multiplicities. To be is to be always already entangled in meshworks of dense meanings and significations. The ruin, far from being an impoverished site or non-place, is an excessive place rich in materiality and meaning, though its qualities are, for the most part, inaccessible to human actants. By recognizing the independence (and interdependence) of objects, we too may become hospitable agents. Keywords: ethics, excessive place, materiality, ruins, speculative realism, waste